Terrorist transgressions gender and the visual culture of the terrorist - Malvern, Sue 1951-; Koureas, Gabriel (International library of cultural studies, 2014)
Terrorism has a variety of contexts, histories and forms which have all been the focus of intense scrutiny in recent years, whilst cultural representations of the terrorist have received much less attention, which is odd when we consider that terrorism by its very nature is spectacle.